A comparative study of Desarda’s mesh free inguinal hernia repair with modified Bassini’s repair - Hosni Mubarak Khan (Digital ProScholar Media, 2021)
Objective. This is a prospective study of 50 cases of inguinal hernias which were treated through open inguinal hernia repair techniques. The study was conducted with the objective of comparing the effectiveness of these procedures and complications. Materials and Methods. A number of 50 cases of inguinal hernias admitted to Dr. BR Ambedkar Medical College and Hospital were selected on the basis of the non-probability (purposive) sampling method. All the patients with direct and indirect uncomplicated hernias treated by means of an open approach were included. After the preoperative preparation, they were randomly chosen either for Desarda’s or Modified Bassini’s repair techniques. Results. In the postoperative period, moderate pain was experienced by 19 patients included in the Desarda group and 17 patients included in the Modified Bassini’s repair group on day 1. The postoperative wound infection developed in 2 cases of Desarda and 3 cases of Modified Bassini’s, erythema was observed in 2 cases of Desarda and 3 cases of Modified Bassini’s, 3 cases reported the occurrence of seroma in the Desarda group and 4 cases of seroma were recorded in the Modified Bassini’s group. Conclusions. The patients who underwent Desarda repair complained of a higher intensity of pain, which could probably be attributed to the extensive dissection involved. The duration of Desarda repair was longer due to the learning curve of the surgeons in our hospital. The return to normal gait and normal activities was significantly lower in the Desarda group. The duration of hospital stays and the postoperative complications was not significantly different in the two groups. There were no recurrences in either of the groups until the current study.